About the ore conduits at the near-surface deposits of gold-silver ores - E. M. Necrasov; L. A. Dorozhkina (Известия высших учебных заведений: Геология и разведка)
It is shown that at the rather numerous near-surface gold-silver ore deposits (sometimes with tellurides), developed in the East of Russia, the fractured ore conduits can be revealed. From them, the bundles and a series of vein-veinlet ore bodies or metasomatic gold-bearing rocks start. In both cases the areas with bonanza contents of the noble metals are established. The portion of their stocks sometimes reaches 70% in a total. Exploration drilling along the barren flanks of the ore-conducting channels can identify new ore, hidden in the depth interval from 100-200 to 400 meters or more, and replenish stocks of the deposits.